Evaluating the teaching competencies of teachers of physical education and sports for the Inter médiate éducation Stage in light of the second generation of the Algerian educational reform - Bengueneb, Abdarahmane; Atallah, ahmed; Bendehiba, Djourdem (sports creativity, 2025)
The study aimed to evaluating the teaching competencies of teachers of physical education and sports in the middle stage in light of the second generation of educational reforms by identifying the most important teaching competencies needed to be available to teachers of physical education and sports, and in the end to determine the extent of the ability of the professor of physical education and sports On employing these competencies within the class, the research team used the descriptive approach to suit the problem of the study, and the study sample included 40 teachers of physical education and sports for the intermediate stage, and they were randomly selected, We used a questionnaire for the teaching competencies as a tool to collect data, and we used the statistical packages program Spss as a statistical tool. And we reached the level of each of the teaching competencies (planning, executive, evaluation, and professional) of physical education and sports teachers in the intermediate education stage in light of the second generation of educational.